Development and usability evaluation of HOPE: A patient-centered mHealth application for HTN self-management in Iran - Mohammad Hosein Hayavi-Haghighi; Abdullah Gharibzade; Zahra Mastaneh; Haniyeh Ansarifard (PLoS ONE, 2026)
Background Hypertension (HTN) is a major global health problem and a significant risk factor for cardiovascular disease. Mobile health (mHealth) applications offer an efficient, patient-centered approach to managing chronic conditions like HTN. Given the high prevalence of HTN in Iran, and a recognized lack of approved and scientifically-grounded mHealth applications, this study aimed to address this gap, particularly in Hormozgan Province. Objective This study aimed to design and evaluate a HTN self-care application, named HOPE, to facilitate self-management and enable patients to access health services outside of clinical settings. Materials and methods The research was conducted in four steps: (1) determination of data elements and functional requirements based on a systematic review of guidelines and feedback from 25 cardiologists and 50 patients using a Likert scale questionnaire; (2) content design based on national and international clinical and educational standards; (3) application development using Visual Studio, ASP.NET framework with MVC architecture, and C#; and (4) usability assessment. The final evaluation involved 46 participants with HTN from the Hormoz Clinic, who used the application for one month, followed by an assessment using the Mobile Application Usability Questionnaire (MAUQ). Results The HOPE application was designed with nine main tabs and 52 sub-tabs, covering key areas such as demographic information, comprehensive education, nutrition tracking, BP recording, medication management, and a dialogue panel for communication with the doctor. The overall usability evaluation for the application yielded an average score of 4.32 (on a 5-point Likert scale), which was categorized as a “very good” level. The highest average score (4.37) was assigned to the “User Interface and Satisfaction” dimension. A significant relationship was determined between satisfaction with the user interface and the participants’ level of education (P > 0.05). Conclusion The HOPE demonstrated very good usability across all evaluated dimensions—ease of use, interface quality, and usefulness. The strong usability performance suggests that the application is well-designed and has high potential to effectively enhance self-care practices and could be a valuable tool in digital health management programs for patients with HTN. Future research should explore the long-term impacts of using HOPE on clinical outcomes and patient adherence, as well as its integration into routine healthcare practice to optimize HTN management.